Assistance in Processing Plastic Waste into Paving Blocks as a Plastic Waste Reduction Strategy in Blimbing Village Besuki District Situbondo Regency - Jaya Hartono; Alya Novia Nurazizah; Karina Paramitha Yanuari; Qonita Hafidah Aseni; Ratna Endang Widuatie (Institut Nalanda, 2023)
Garbage is the result of daily human activities or natural processes in the form of solid or semi-solid in the form of organic and inorganic. Therefore, all activities carried out by humans certainly produce various types of waste, one of which is inorganic waste such as plastic. The problem studied in this study is the process of managing plastic waste by the people of Blimbing Village, Besuki District, Situbondo Regency, which is still not good, because of that researchers innovated in the form of processing plastic waste into paving blocks. The purpose of this research is to build a village free of plastic waste and invite the people of Blimbing Village to process plastic waste into goods that have a selling price. This research is a type of qualitative research which is based on direct observation at the research location. Efforts to process plastic waste into paving blocks are carried out so that the people of Blimbing Village care more about environmental cleanliness and increase people's creativity in processing waste.